2019
DOI: 10.1101/630533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Health literacy assessment of primary care patients in Low and Middle Income Countries”

Abstract: Background: Health literacy includes cognitive and social skills which help patients to access, understand and use medical information in ways that promote and maintain good health. Recently health literacy emerged as an important topic for public health and health policy makers.Objectives: This study was designed to evaluate health literacy level among patients of primary care centers in Prishtina and its association with socioeconomic status, education level, hospitalization rates, self-perception on health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…It is, however, dissimilar with findings of Pasha et al who had more primary care patients (28.54%) in the 26-35 age category 18. …”
contrasting
confidence: 86%
“…It is, however, dissimilar with findings of Pasha et al who had more primary care patients (28.54%) in the 26-35 age category 18. …”
contrasting
confidence: 86%
“…We found several studies that focused on general population HL [ 12 , 14 , 16 , 18 , 19 , 20 ]; however, we found fewer data about the health literacy level of medical/health sciences professionals and students [ 17 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 92%
“…Addressing the inequalities in health and health care is important for supporting patients with a low level of health literacy [26]. In Makassar, a city in Indonesia, one study reported on the effectiveness of the precede-proceed education model in improving functional health literacy [27].…”
Section: Discussionmentioning
confidence: 99%